Analysis of Customer Satisfaction With Non-Subsidized Fuel at Pertamina SPBU In Pelalawan Regency – Riau Province - ., Johan; ., Zulkarnain; Alwie, Alvi Furwanti; ., Samsir (Journal of Ecohumanism, 2024)
This study aims to develop a new conceptual model of how green marketing, e-WOM, and service quality affect brand image and how it affects customer satisfaction. Customer BBM Pertamax series and PERTAMINA Dex products. This research can fill the limitations of previous research and the research gaps on customer satisfaction. This quantitative study collected data through questionnaires distributed to customers of BBM Pertamax series and Pertamina Dex products in Pelalawan Regency, Riau Province. The sample calculation used a formula that produced 360 respondents using a purposive random sampling approach. A Likert-scale questionnaire was used to collect data, and SmartPLS 4.0 was used to process it. The findings include that green marketing has a positive and significant effect on brand image; e-wom has a positive and significant effect on brand image; service quality has a significant positive effect on brand image; green marketing has a positive and significant effect on customer satisfaction; e-wom has a positive but not significant effect on customer satisfaction; service quality has a significant positive effect on customer satisfaction. Brand image can significantly mediate the effect of green marketing on customer satisfaction; the brand image can significantly mediate the effect of service quality on customer satisfaction; the Brand image can mediate the effect of e-WOM on customer satisfaction; and brand image has a positive and significant effect on customer satisfaction.